Implications of Control of Coastal Lands by Foreigners in The Tourism Business - Putu Ayu Sriasih Wesna; Leonito Ribeiro (Postgraduated Community Service Journal, 2022)
This article analyzes the "Implications of Coastal Land Tenure By Foreigners in the Tourism Business." The focus of the study in this paper is the legal aspects of coastal land control by foreigners in Bali to benefit the tourism business. In analyzing these legal issues, the author uses empirical legal research methods with a statutory approach, a conceptual approach, a sociological approach, and a case approach. Based on the theory of authority, the theory of expediency, and the theory of legal protection as an analytical knife, the tourism business in Bali cannot be separated from the existence of foreigners. Similarly, the control of coastal land in Bali-pun does not escape the control of foreigners, both through legal investment and some illegal, by utilizing mutually beneficial cooperation between residents and with prajuru Indigenous Villages on the basis of sharing profits. Balinese people who have a unique culture with nuances of Hinduism in daily life and in running a business in the field of tourism are always based on the "Tri Hita Karana Philosophy" which is manifested in behavior that significantly maintains a harmonious relationship between "Man with God" Man with Nature, and "Humans with other Humans." It is in this philosophy that the principle of good faith in investing is reflected so that the possession of coastal lands by foreigners for the benefit of the tourism business is obliged to respect this very noble principle; however, in empirical facts, it turns out that the control of coastal lands in Bali by foreigners under the guise of mutually beneficial cooperation is likely to harm the use of indigenous villages in carrying out the religious values attached to these coastal lands. So that in this case, the concept of mutually beneficial cooperation is contained in the lousy faith of foreigners to control the land of Bali to get personal benefits at the expense of Balinese nature wrapped in mutually beneficial Works.